2001
DOI: 10.1161/hq1201.100258
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Whole Grain and Legume Powder Reduces Insulin Demand, Lipid Peroxidation, and Plasma Homocysteine Concentrations in Patients With Coronary Artery Disease

Abstract: Abstract-Our objective was to evaluate whether isocaloric replacement of refined rice with whole grains and other plant products as a form of powder reduces coronary artery disease (CAD) risk factors, such as insulin demand and lipid peroxidation in CAD patients. Seventy-six male patients with CAD were randomly assigned to either a group ingesting a whole-grain meal daily or a control group for 16 weeks. In the whole-grain group, serum concentrations of glucose and insulin decreased by 24% and 14%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 32 publications
3
112
2
Order By: Relevance
“…Of these reports, 226 were excluded based on other criteria, leaving 41 trials (39 reports) that satisfied the inclusion criteria but did not meet the exclusion criteria, of which 11 trials (ten reports) investigated pulses alone, 19 trials (19 reports) investigated pulses in a low-GI dietary intervention, and 11 trials (ten reports) investigated pulses in a high-fibre dietary intervention. Tables 1, 2, and 3 show the characteristics of the 41 randomised controlled experimental trials included in each of the three meta-analyses: pulses alone [45][46][47][48][49][50][51][52][53][54], pulses in low-GI diets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and pulses in highfibre diets [55][56][57][58][59][60][61][62][63][64]. The 11 trials (ten reports) investigating pulses alone (Table 1) were predominantly crossover in design (seven trials, five of which had a washout period), studied a total of 253 participants (type 2 diabetes, n=21; normoglycaemia and/or hypercholesterolaemia, n=232) and had a mean sample size of 23.…”
Section: Methodsmentioning
confidence: 99%
“…Of these reports, 226 were excluded based on other criteria, leaving 41 trials (39 reports) that satisfied the inclusion criteria but did not meet the exclusion criteria, of which 11 trials (ten reports) investigated pulses alone, 19 trials (19 reports) investigated pulses in a low-GI dietary intervention, and 11 trials (ten reports) investigated pulses in a high-fibre dietary intervention. Tables 1, 2, and 3 show the characteristics of the 41 randomised controlled experimental trials included in each of the three meta-analyses: pulses alone [45][46][47][48][49][50][51][52][53][54], pulses in low-GI diets [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and pulses in highfibre diets [55][56][57][58][59][60][61][62][63][64]. The 11 trials (ten reports) investigating pulses alone (Table 1) were predominantly crossover in design (seven trials, five of which had a washout period), studied a total of 253 participants (type 2 diabetes, n=21; normoglycaemia and/or hypercholesterolaemia, n=232) and had a mean sample size of 23.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance was quantified by the glucose area under the curve (AUC) obtained during the oral glucose tolerance test as described previously. 24 …”
Section: Analysesmentioning
confidence: 99%
“…Comparison of net differences between the two groups showed that the glucose and insulin response areas following an OGTT were lower in nondiabetic subjects after receiving the powder breakfast. Using the homeostasis model assessment (HOMA), insulin resistance and b-cell function were improved in the powder group relative to the control group in nondiabetic subjects (Jang et al, 2001). Pereira et al compared insulin sensitivity in overweight people with T2DM on diets that incorporated refined or whole grains.…”
Section: Short-and Medium-term Dietary Intervention Studiesmentioning
confidence: 99%